2017
DOI: 10.1080/14606925.2017.1352653
|View full text |Cite
|
Sign up to set email alerts
|

Preparing design students for the market: an initial investigation on the required knowledge and skills for graphic designers in Brazil

Abstract: How design professionals are trained-knowledge and skills acquiredaffects directly the contribution provided for companies. In this paper, we report an initial investigation in how academics (students and teachers) and market (companies) value different skills in graphic design professionals. Through a survey with students, teachers and companies in Brazil, we unveil the relevance of 25 skills for both students, teachers and companies. Then, we compared those groups to find differences in how the skills were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
2
5
0
1
Order By: Relevance
“…For example, references to knowledge in 'Business', 'Problem solving' and 'User Experience' were present in less than five percent of the advertisements in our data set. The results of our study are similar to the outcome of the survey by Dziobczenski and Galeotti (2017) in which Brazilian companies reported to value the tactical and operational skills of designers (i.e. software and layout skills), while more strategic design skills such as business and leadership were found less valued.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, references to knowledge in 'Business', 'Problem solving' and 'User Experience' were present in less than five percent of the advertisements in our data set. The results of our study are similar to the outcome of the survey by Dziobczenski and Galeotti (2017) in which Brazilian companies reported to value the tactical and operational skills of designers (i.e. software and layout skills), while more strategic design skills such as business and leadership were found less valued.…”
Section: Discussionsupporting
confidence: 86%
“…The authors also found that design graduates were seen to hold adequate skills in areas such as design and visual methodology, software and ergonomics. Similarly, in assessing how Brazilian academics (students and teachers) and companies value different design skills, Dziobczenski and Galeotti (2017) found that designers are highly valued for their tactical and operational skills (i.e. software and layout skills), while more strategic design skills, such as business and leadership skills, were less valued by companies.…”
Section: Introductionmentioning
confidence: 99%
“…Incompetent performance of graduates in the workforce is believed to be the main cause of this conflict (Bridges, 2013;Cheung, 2011). Previous studies exemplified that both parties have different expectations when it comes to what types of knowledge, skills, and abilities should be possessed by GD graduates to perform effectively in the industry (e.g., Cheung, 2016;Dziobczenski & Galeotti, 2017;Wang, 2006). Nevertheless, it is not wise to isolate the industry's expectations from design education or vice versa (Butler, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies had been conducted to identify the knowledge, skills, traits, and abilities required by GD graduates in different geographical regions (e.g., Bridges, 2013;Cheung, 2016;Dharavath, 2003;Dziobczenski & Galeotti, 2017;Hsieh, Guan & Wu, 2010;Wang, 2006;Wilson, 2014), ethics and values are being paid relatively less explicit attention in these studies. However, design scholars (e.g., Berman, 2009;Heller & Vienne, 2003;McCollam, 2014;Perkins, 2011) and design associations (e.g., AIGA, 2010;wREGA, 2012;International Council of Design (ico-D), 2011;GDC, 2012) have highlighted their significance to professional practice and development in the GD field.…”
Section: Introductionmentioning
confidence: 99%
“…Cranmer 2006; Doloswala et al . 2013; Dziobczenski & Galeotti 2017; Tymon 2013). A branch of this research examines job advertisements to establish what skills, capacities and attributes employers expect, including in architecture (Salleh et al .…”
Section: Introductionmentioning
confidence: 99%